Effects of Abrupt Variations of Solar Wind Dynamic Pressure on the High-Latitude Ionosphere - Igino Coco; Ermanno Amata; Maria Federica Marcucci; Danila Ambrosino; Simon G. Shepherd (International Journal of Geophysics)
We show the results of a statistical study on the effects in the high-latitude ionosphere of abrupt variations of solar wind dynamic pressure, using Super Dual Auroral Radar Network (SuperDARN) data in both hemispheres. We find that, during periods of quiet ionospheric conditions, the amount of radar backscatter increases when a variation in the dynamic pressure occurs, both positive (increase of the pressure) and negative (decrease of the pressure). We also investigate the behaviour of the Cross-Polar Cap Potential (CPCP) during pressure variations and show preliminary results.